2012
DOI: 10.1007/978-3-642-25076-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Hopping Mechanism

Abstract: In the limit of strong electron-phonon coupling and weak intermolecular electronic coupling, a charged molecule undergoes a large geometry relaxation, which eventually traps the charge. In this case, the charge transport can be viewed as an intermolecular hopping process. With the known electron transfer rates between neighboring molecules, the charge carrier mobility can be evaluated through the Einstein relation from random walk simulations. In general, the classical Marcus electron transfer theory, which wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It is suggested that in an extreme case, when the fluctuation in the transfer integral is larger than its average, the dynamic disorder can even increase the hole mobility for 2D materials within the ab-plane. 59 Nevertheless, despite of its limitation, Marcus theory has been widely used to describe the charge transfer mechanism in various organic materials at room temperature and shows good agreement with the experiments. 36,38,60 The inclusion of dynamic disorder will be considered in our future work for further improvement of the calculated mobility in organic semiconductors.…”
Section: Reorganization Energy and Hole Mobilitymentioning
confidence: 97%
See 1 more Smart Citation
“…It is suggested that in an extreme case, when the fluctuation in the transfer integral is larger than its average, the dynamic disorder can even increase the hole mobility for 2D materials within the ab-plane. 59 Nevertheless, despite of its limitation, Marcus theory has been widely used to describe the charge transfer mechanism in various organic materials at room temperature and shows good agreement with the experiments. 36,38,60 The inclusion of dynamic disorder will be considered in our future work for further improvement of the calculated mobility in organic semiconductors.…”
Section: Reorganization Energy and Hole Mobilitymentioning
confidence: 97%
“…A phonon-assisted term needs to be added to the temperature dependence of mobility. 59 However, such type of calculation is computationally expensive in the study of 3P-10P or even larger phenacene structures. It is suggested that in an extreme case, when the fluctuation in the transfer integral is larger than its average, the dynamic disorder can even increase the hole mobility for 2D materials within the ab-plane.…”
Section: Reorganization Energy and Hole Mobilitymentioning
confidence: 99%